THE EFFECT OF SUGGESTOPEDIA IN VOCABULARY LEARNING TOWARDS INDONESIAN MADRASAH STUDENTS - Tajariana Tajariana; Muhammad Zuhri Dj.; Musfirah Musfirah (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The aim of this research is to improve students' vocabulary by Suggestopedia method where students can be more relaxed but stay focused in learning. This method is more to encourage students to have the suggestion that learning English is fun then, to find out where the students' vocabulary is using this method. The sample of this research is the eleventh-grade students in MA Daarul Quran Pajalele. The selected sample technique used is total sampling consisting of 16 students to learn English using instrumental music, stories, dialogue as one example of the suggestopedia method. This research is quantitative approach. The researchers use vocabulary test and multiple choice as vocabulary measurement tools known by students. Results of students' average scores before and after treatment, the mean score obtained by students in the post-test (85.94) is greater from the average grade of students in the pre-test (45.31). It is assumed that through this suggestopedia method very helpful to improve students’ vocabulary.